Adab Bermedia Sosial dalam Persfektif Islam Pada Pembelajaran Akidah Akhlak - Anisa Rahmatul Meiril; Mislaini M; Koriyati Berliyan Niltasari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid development of social media has transformed students' patterns of communication, social interaction, and behavior. While social media facilitates access to information, it also gives rise to various ethical issues, including the spread of misinformation (hoaxes), hate speech, cyberbullying, and slander. These challenges highlight the importance of strengthening character education based on Islamic values through Aqidah Akhlak learning. This article aims to analyze the concept of social media ethics from an Islamic perspective and its implementation in Aqidah Akhlak learning. The study is based on an analysis of the Qur'an, the Hadith of Prophet Muhammad (peace be upon him), Qur'anic commentaries (tafsir), Islamic education literature, and relevant scholarly journals. The findings reveal that Islamic social media ethics are founded on the principles of tabayyun (information verification), maintaining ethical speech and writing, avoiding ghibah (backbiting), slander, and hate speech, as well as promoting the dissemination of truthful and beneficial information. The implementation of these values in Aqidah Akhlak learning is carried out through curriculum integration, contextual learning, discussions, case studies, habituation, and teachers' exemplary conduct. Therefore, Aqidah Akhlak learning plays a significant role in developing students with noble character, digital literacy, and the ability to use social media wisely in accordance with Islamic values.